Virtual reality technology: How can it help us understand decision-making in sport? - Craig, C.; Cummins, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
To properly understand expertise and decision-making in sport we need a methodology that can adequately and accurately recreate the perception/action cycle and allow us to measure and understand decision-making from the player`s perspective. In other words, we need to use technology that allows us to recreate an athlete`s (egocentric) 3D perspective of an unfolding sports related event that can be updated in real time (Bideau et al, 2010). At the same time it has to also offer the possibility of precisely controlling the perceptual information presented to the observer immersed in the environment and reliably reproduce these conditions across trials. The experience has to also be interactive, so that we can record how the observer interacts or responds to the information presented in the environment. Immersive, interactive virtual reality technology offers an exciting new way of studying decision making in sport where the perception/action cycle is maintained (Craig, 2014). The versatility of this technology means it can be easily applied to many different sports (e.g. rugby (Brault et al, 2012), soccer (Dessing & Craig, 2010), cricket (Dhawan et al, 2015)). In this talk I will present different examples from different sports and show systematically how the dynamics of the visual information presented to players influences decisions about when and how to act. I will also explore how an in-depth analysis of the movement of a player as an event unfolds provides valuable insight into expert/novice differences in the decision-making process (Craig & Watson, 2011). ABSTRACT FROM AUTHOR